A vállalati vagyon és a finanszírozás összefüggései a vagyonértékelés szempontrendszere szerint - Buzás, Ferenc; Kis, S.; Mező, I. (International Journal of Engineering and Management Sciences, 2017)
The availability for financial sources can be the key factor of competitiveness of enterprises. Under favourable conditions it can result in not only economic growth and conjunctural effects but indirectly it also has a positive influence on social level as well. In the first part of the article we make an overview on enterprise financing in both social and economic context and try to give an overall concept. In the second part we analyse the framework of financing, discuss the national and international specifications of financing, and finally, in the third part we analyse the background of enterprise financing based on the principles of asset appraisal.